Use of Polymerase Chain Reaction Enzyme Linked Oligonucleotide Sorbent Assay (Pcr-Elosa) for Detection of Disease Agents - Tarigan, Simson (Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Diagnostic tool comprises one of the vital components in the control of infectious diseases. One of the most common techniques in the diagnosis of infectious disease currently available is the polymerase chain reaction (PCR) because this technique is very sensitive, specific, and rapid. This technique requires an adjunct technique to indicate the formation of the right reaction product. Agarose gel electrophoresis has been the most common technique to visualise the PCR product or amplicon. Enzyme linked oligonucleotide sorbent assay (ELOSA) is an alternative technique which is more sensitive and gives more important identity of the amplicon. This technique can be more than 100 times as sensitive as a gel agarose electrophoresis, and very specific since confirmation of the amplicon is carried out by DNA hibridisation. The capacity of the ELOSA can also be extended to the detection of disease-causal agent at subtype level, or detection of mutation at particular location in a gene. Since the equipment used for ELOSA is similar to that for ELISA (enzyme linked immunosorbent assay), a large number of samples can be accomplished rapidly. As in ELISA, a number of variation can be made in ELOSA depend on the requirement. Nucleotide can be immobilised on the microwell plate either by passive adsorbtion, by first conjugation of nucleotide with biotin then immobilisation on streptavidin-coated microwell plate, or immobilisaion by covalent bonding. The PCR and ELOSA can be performed at separate or in a single tube by first immobilising the PCR primers on the surface of microwell plates. Key words: PCR amplicon, agarose electrophoresis, oligonucleotide immobilisation, DNA hybridisation